Prevalence and molecular characteristics of polymyxin-resistant Enterobacterales in a Chinese tertiary teaching hospital - Xiao, Chenlu; Li, Xuming; Huang, Lianjiang; Cao, Huiluo; Han, Lizhong; Ni, Yuxing; Xia, Han; Yang, Zhitao (Frontiers in Cellular and Infection Microbiology, 2023)
Polymyxin-resistant Enterobacterales poses a significant threat to public health globally, but its prevalence and genomic diversity within a sole hospital is less known. In this study, the prevalence of polymyxin-resistant Enterobacterales in a Chinese teaching hospital was investigated with deciphering their genetic determinants of drug-resistance. Polymyxin-resistant Enterobacterales isolates identified by MALDI-TOF MS were collected in Ruijin Hospital from May to December in 2021. Both Vitek-2 Compact and broth dilution method were used to determine the polymyxin B (PMB) susceptibility. Polymyxin-resistant isolates were further characterized by molecular typing using PCR, multi-locus sequence typing (MLST) and sequencing of the whole genome. Of the 1,216 collected isolates, 32 (2.6%) isolates across 12 wards were polymyxin-resistant (MIC range, polymyxin B 4 -256 μg/l and colistin 4 - ≥16 μg/l). Twenty-eight (87.5%) of the polymyxin-resistant isolates had a reduced susceptibility to imipenem and meropenem (MIC ≥ 16 μg/ml). Of the 32 patients, fifteen patients received polymyxin B treatment and 20 patients survived before discharge. The phylogenetic tree of these isolates showed these isolates blonged to different clones and multiple originated. The polymyxin-resistant K. pneumoniae isolates belong to ST11, ST15 (10.71%) and ST65 (3.57%), and the polymyxin-resistant E.coli beleng to four different ST-69 (25.00%), ST-38 (25.00%), ST-648 (25.00%) and ST-1193 (25.00%). In addition, six mgrB pecific mutations (snp_ALT c.323T>C and amino acid change p.Val8Ala) were identified out in 15.6% (5/32) isolates. Mcr-1, a plasmid-mediated polymyxin-resistant gene, was found exist in 3 isolates and nonsynonymous mutations, including T157P, A246T, G53V and I44L, were also observed. In our study, a low prevalence of polymyxin-resistant Enterobacterales was observed, but these isolates were also identified as multi-drug resistant. Therefore, efficient infection control measures should be implemented to prevent the further spread of resistance to the last-line polymyxin therapy.